Subnational analyses using the Luxembourg Income Study (LIS) data archive - David K. Jesuit (Luxembourg Income Study (LIS), 2008)
This brief chapter introduces researchers to the possibilities for subnational research using the harmonized data sets made available via the Luxembourg Income Study (LIS) (www.lisproject.org). We first offer a brief overview of the LIS and discuss specific challenges for subnational research using LIS microdata. Next, we review some of the contributions LIS data and researchers have made in the comparative study of subnational poverty and income inequality. Finally, we conclude with a brief presentation of the most recent poverty rates for German Länder and Italian Regions derived from the LIS. It is hoped that this introduction will provide scholars with a resource that will foster subnational examinations of economic well-being.
Keywords: 330; Haushaltseinkommen; Datenerhebung; Armut; Einkommensverteilung; Teilstaat; Deutschland; Italien